2021
DOI: 10.4329/wjr.v13.i6.192
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in the COVID-19 era: Lessons learned during a pandemic

Abstract: The first year of the coronavirus disease 2019 (COVID-19) pandemic has been a year of unprecedented changes, scientific breakthroughs, and controversies. The radiology community has not been spared from the challenges imposed on global healthcare systems. Radiology has played a crucial part in tackling this pandemic, either by demonstrating the manifestations of the virus and guiding patient management, or by safely handling the patients and mitigating transmission within the hospital. Major modifications invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 204 publications
(302 reference statements)
1
7
0
1
Order By: Relevance
“…We fully agree with these studies [ 46 , 47 , 48 , 49 , 50 ]. We believe that challenges and acceptance of the integration of technology must be interconnected and go hand in hand so that expectations are not disillusioned, and we can obtain Artificial Intelligence that offers us an increasingly effective and health-oriented useful approach.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We fully agree with these studies [ 46 , 47 , 48 , 49 , 50 ]. We believe that challenges and acceptance of the integration of technology must be interconnected and go hand in hand so that expectations are not disillusioned, and we can obtain Artificial Intelligence that offers us an increasingly effective and health-oriented useful approach.…”
Section: Discussionsupporting
confidence: 92%
“…A Sentiment analysis review conducted on Twitter showed an increasing attention on the integration of Artificial Intelligence in Digital Radiology [ 46 ]. Other review studies clearly showed that the pandemic represented an important engine for the development of this field [ 47 , 48 , 49 ] and an important lesson on how to continue for the future, as highlighted in the perspective reported in [ 37 ]. Other studies considered Artificial Intelligence in Digital Radiology in terms of impact to equity [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hospitals and health centers reduced their functioning capacity to maintain social distancing measures in accordance with government guidelines, which consequently delayed cancer diagnosis. Furthermore, any staff who displayed symptoms/tested positive for COVID-19 (or were exposed to someone who has tested positive) were also required to self-isolate as part of government guidelines, which further disrupted staffing levels and limited functioning capacity [ 18 ]. The UK NHS operational standard for the 2 week-wait urgent referral system states that 93% of patients with suspected cancer should be seen by a specialist within 14 days from primary care referral.…”
Section: Impact On the Investigation Of Patients With Suspected Cancermentioning
confidence: 99%
“…A deep analysis conducted on social media highlighted a growing attention on the integration of AI in DR within the health domain [ 32 ]. Surely, the COVID-19 pandemic that people are experiencing has also represented an important push in this direction [ 37 , 38 , 39 ] and given an important lesson for the future [ 40 ]. An improvement in equity of care is also expected from the integration of AI in DR into the health domain [ 41 ].…”
Section: Discussionmentioning
confidence: 99%